Mentalization in adults with attention deficit hyperactivity disorder: Comparison with controls and patients with borderline personality disorder. (October 2017) - Perroud, Nader; Badoud, Deborah; Weibel, Sébastien; Nicastro, Rosetta; Hasler, Roland; Küng, Anne-Lise; Luyten, Patrick; Fonagy, Peter; Dayer, Alexandre; Aubry, Jean-Michel; Prada, Paco; Debbané, Martin
Abstract: Emotion dysregulation and interpersonal hardships constitute core features of borderline personality disorder (BPD). Research has established the link between these core dysregulations and fluctuations in the capacity to appreciate the mental states that underlie behavior (mentalizing, operationalized as reflective functioning (RF)). As emotion dysregulation and interpersonal hardships also characterize adults with attention deficit hyperactivity disorder (ADHD), this study sought to examine the potential RF impairments affecting this population. 101 adults with ADHD, 108 with BPD and 236 controls were assessed using the RF questionnaire (RFQ), evaluating how individuals employ information about mental states to better understand their own and others' behaviors. The RFQ comprises two dimensions, certainty (RF_c) and uncertainty (RF_u) about mental states. RF scores helped distinguish ADHD from controls, but also from BPD (F = 48.1(2/441) ; p < 0.0001 for RF_c and F = 92.5(2/441) ; p < 0.0001 for RF_u). The ADHD group showed intermediary RF scores compared to the controls (b = −0.70; p < 0.0001 and b = 0.89; p < 0.0001 for RF_c and RF_u) and BPD group (b = 0.44; p = 0.001 and b = −0.56; p = 0.001 for RF_c and RF_u). Lower RF scores correlated with poor anger control and high levels of impulsivity. Higher severity of ADHD (more attentional and hyperactive/impulsive symptoms) was correlated with RF impairments. In conclusion, RF may constitute an important process underlying attentional, hyperactive/impulsive as well as emotional symptoms in ADHD; it should therefore be considered in the assessment of these patients. Highlights: Mentalizing helped distinguishing ADHD from controls and BPD. Mentalizing in ADHD and BPD correlated with poor anger control and high impulsivity. Severity of ADHD symptoms, was positively related to impairments in mentalizing.